Stimulatory and Inhibitory Roles of Brain 2-Arachidonoylglycerol in Bombesin-Induced Central Activation of Adrenomedullary Outflow in Rats - Takahiro Shimizu; Kenjiro Tanaka; Kunihiko Yokotani (Elsevier, 2013)
2-Arachidonoylglycerol (2-AG) is recognized as a potent endocannabinoid, which reduces synaptic transmission through cannabinoid CB1 receptors, and is hydrolyzed by monoacylglycerol lipase (MGL) to arachidonic acid (AA), a cyclooxygenase substrate. We already reported that centrally administered MGL and cyclooxygenase inhibitors each reduced the intracerebroventricularly (i.c.v.) administered bombesin-induced secretion of adrenal catecholamines, while a centrally administered CB1-antagonist potentiated the response, indirectly suggesting bidirectional roles of brain 2-AG (stimulatory and inhibitory roles) in the bombesin-induced response. In the present study, we separately examined these bidirectional roles using 2-AG and 2-AG ether (2-AG-E) (stable 2-AG analog for MGL) in rats. 2-AG (0.5 μmol/animal, i.c.v.), but not 2-AG-E (0.5 μmol/animal, i.c.v.), elevated basal plasma catecholamines with JZL184 (MGL inhibitor)- and indomethacin (cyclooxygenase inhibitor)-sensitive brain mechanisms. 2-AG-E (0.1 μmol/animal, i.c.v.) effectively reduced the bombesin (1 nmol/animal, i.c.v.)-induced elevation of plasma catecholamines with rimonabant (CB1 antagonist)-sensitive brain mechanisms. Immunohistochemical studies demonstrated the bombesin-induced activation of diacylglycerol lipase α (2-AG-producing enzyme)-positive spinally projecting neurons in the hypothalamic paraventricular nucleus, a control center of central adrenomedullary outflow. These results directly indicate bidirectional roles of brain 2-AG, a stimulatory role as an AA precursor and an inhibitory role as an endocannabinoid, in the bombesin-induced central adrenomedullary outflow in rats. Keywords:: 2-arachidonoylglycerol, monoacylglycerol lipase, cyclooxygenase, cannabinoid CB1 receptor, central adrenomedullary outflow